2018
DOI: 10.1159/000487820
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Submucosal Dissection for the Treatment of Superficial Epithelial Gastric Neoplasia in a Portuguese Centre

Abstract: Background: The emergence of endoscopic submucosal dissection (ESD) made possible en bloc resection of neoplastic gastric lesions, regardless of lesion size, with reduced rates of complications and recurrence. This technique has become the preferred method for curative resection, instead of conventional endoscopic mucosal resection and surgery, when distant metastases have negligible risk. In Western countries experience with this technique has evolved quickly, with an increasing number of case series reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…It can not only clarify the pathological diagnosis, but can also effectively reduce the incidence of recurrence and metachronous cancers (5), while retaining the original physiological structure. Compared with traditional surgery, there are fewer complications after ESD, and the patient's quality of life is enhanced (6).…”
Section: Introductionmentioning
confidence: 99%
“…It can not only clarify the pathological diagnosis, but can also effectively reduce the incidence of recurrence and metachronous cancers (5), while retaining the original physiological structure. Compared with traditional surgery, there are fewer complications after ESD, and the patient's quality of life is enhanced (6).…”
Section: Introductionmentioning
confidence: 99%
“…This work has been developed by several Portuguese gastroenterologists during the last years [3][4][5][6][7][8]. The improvement in R0 resection rates in the study by Costa et al [2] may reflect improvements in all these factors.…”
mentioning
confidence: 97%
“…In this issue of GE -Portuguese Journal of Gastroenterology, Costa et al [2] report on the results of 114 gastric ESDs performed in a high-volume center in Portugal. Authors found that gastric ESD is associated with en bloc resection in 96% of all cases, corresponding to R0 resections in 88%, a curative resection was obtained in 83.2%.…”
mentioning
confidence: 99%
“…No previous Portuguese ESD series included underwater duodenal ESD [4][5][6][7]. However, when EMR is not possible, and considering the potentially aggressive surgeries, this can be attempted by experienced endoscopists in ESD.…”
mentioning
confidence: 99%